Pendidikan Desa Berkualitas : Revitalisasi Taman Baca Desa Jambu Bengkulu Mencapai Sustainable Development Goals - Ririn Nopiah; Lela Rospida; Yusnida (UNIB Press, 2022)
Sustainable Village Development / SDG's Village is a big program for Indonesia. One of SDG's Village programs is quality village education. Desa Jambu in Bengkulu City is one of the villages that has a high opportunity to become a role model for SDG's Village achievements with the existence of a Taman Baca Desa system, but the implementation of Desa Jambu Taman Baca program has not been carried out optimally by the Village so that the purpose of this community empowerment activity is to revitalize the Taman Baca Desa to achieve sustainable Development Goal’s. The Empowerment Activities carried out in the form of counseling and socialization of the importance of managing taman baca desa. The results of this activity show that there is interest, enthusiasm and awareness of the importance to manage taman baca desa by good and optimal management for mutual benefit.